Ships & guns : the sea ordnance in Venice and Europe between the 15th and the 17th centuries - Beltrame, Carlo, 1969-; Ridella, Renato Gianni (Oxbow Books, 2011)
Ships and Guns brings together experts from the field of historic artillery and underwater archaeologists to present a series of papers which focus on the development of naval ordnance in Europe and, especially, Venice, in the 15th-17th centuries, as exemplified by the maritime archaeological resource. Subjects include Venetian ordnance in shipwrecks of the Mediterranean and Atlantic, the race to develop big calibres in the first war of Morea, Genoese ordnance aboard galleys in the 16th century, the strategic logistics of guns at sea during the Spanish armada of 1588 and ships and guns of the Tudor navy.